ONTOLOGI TEOSENTRIS DAN RASIONALITAS OTONOM: ANALISA KOMPARATIF-SISTEMATIS FILSAFAT KRISTEN DAN RASIONALISME - Alexander Situmorang; Elis Louisa Ay (Sekolah Tinggi Teologi Hagiasmos Mission, 2026)
The historical tension between faith and reason has remained a central theme in the development of Western philosophy. Christian philosophy and modern rationalism represent two fundamentally different frameworks for understanding reality, knowledge, and truth. Christian philosophy is grounded in a theocentric worldview, wherein God is the ultimate source of all being and knowledge. In contrast, rationalism upholds the autonomy of human reason as the sole foundation for truth and epistemic authority. This article aims to provide a systematic comparison of the ontological and epistemological structures of these two traditions and to explore their implications for human understanding of existence.The study employs a qualitative, comparative-philosophical approach based on library research. It analyzes primary figures such as Augustine and Thomas Aquinas from the Christian tradition, and René Descartes and Baruch Spinoza from the rationalist tradition. The findings reveal that Christian philosophy centers knowledge on the interplay between faith and divine revelation, while rationalism isolates knowledge from divine authority and emphasizes deductive reasoning. These distinctions are not merely methodological but deeply impact each system’s metaphysics and anthropology.The article concludes that both Christian philosophy and rationalism represent comprehensive paradigms with unique strengths and limitations. It recommends a dialogical and integrative approach in contemporary philosophy to bridge the historical divide between faith and reason, especially in addressing today’s epistemological and existential challenges.Keywords: Christian Philosophy, Rationalism, Theocentric Ontology, Faith and Reason